Student Motivation and Interest in Continuing Masters Education during the Covid-19 Pandemic - Ni Luh Made Elisa Intan Apsari; Ni Putu Sri Harta Mimba (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
This research aims to obtain empirical evidence regarding the influence of student motivation on interest in pursuing a master's degree in accounting. Students majoring in the Accounting Study Program at Udayana University batch 2018 are the research population. Probability sampling with simple random sampling was chosen by the researcher as the technique used in selecting the sample which was calculated using the Slovin formula. To collect data used in the form of a questionnaire distributed via google form with multiple linear regression analysis. The findings in this research include career motivation and degree motivation have a significant positive effect, while the perception of cost has a significant negative effect on student interest in pursuing a master's degree in accounting, Faculty of Economics and Business, Udayana University.